Assessment on state’s duty to protect human rights violations by business enterprises within oil & gas industry (O&G) - Ma Kalthum Ishak; Rohaida Nordin (Penerbit Universiti Kebangsaan Malaysia, 2019)
To date, transnational corporations (TNCs), including oil and gas (O&G) companies, have had no direct human rights obligations under international law. International law and human rights law have principally focused on protecting individuals from violations by the government. In view of the recent development, it is timely to have a look into O&G laws in Malaysia. This article presents a brief summary of basic picture of O&G industry in Malaysia. In the first part, it gives a brief introduction of historical development of O&G industry and introduction of United Nations Guiding Principle (UNGP). It also discusses on the role of PETRONAS as the appointed main regulators of O&G industry in Malaysia. It then attempts to lay down the relationship between existing legal frameworks governing the activities in the value chain of the O&G industry in Malaysia and State responsibility to protect under UNGP principle.